2021
DOI: 10.3390/s21082697
|View full text |Cite
|
Sign up to set email alerts
|

Validity of Hololens Augmented Reality Head Mounted Display for Measuring Gait Parameters in Healthy Adults and Children with Cerebral Palsy

Abstract: Serious games are a promising approach to improve gait rehabilitation for people with gait disorders. Combined with wearable augmented reality headset, serious games for gait rehabilitation in a clinical setting can be envisaged, allowing to evolve in a real environment and provide fun and feedback to enhance patient’s motivation. This requires a method to obtain accurate information on the spatiotemporal gait parameters of the playing patient. To this end, we propose a new algorithm called HoloStep that compu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 52 publications
0
9
0
Order By: Relevance
“…In 2016, Microsoft introduced the HoloLens (HoloLens 1st Generation, Microsoft Inc., Redmond, WA), a head-mounted MR system that includes an inertial measurement unit, environment sensing cameras, and a holographic display. A pair of recent studies found the potential utility of the HoloLens as a gait assessment tool to track spatiotemporal gait parameters (Geerse et al, 2020 ; Guinet et al, 2021 ) reporting the system reliable at test-retest parameterization of walking speed (interclass correlation coefficient, ICC = 0.86), cadence (ICC = 0.88), and step length (ICC = 0.77). Additionally, Coolen and colleagues developed a training tool to facilitate virtual obstacle-avoidance training with the HoloLens (Coolen et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…In 2016, Microsoft introduced the HoloLens (HoloLens 1st Generation, Microsoft Inc., Redmond, WA), a head-mounted MR system that includes an inertial measurement unit, environment sensing cameras, and a holographic display. A pair of recent studies found the potential utility of the HoloLens as a gait assessment tool to track spatiotemporal gait parameters (Geerse et al, 2020 ; Guinet et al, 2021 ) reporting the system reliable at test-retest parameterization of walking speed (interclass correlation coefficient, ICC = 0.86), cadence (ICC = 0.88), and step length (ICC = 0.77). Additionally, Coolen and colleagues developed a training tool to facilitate virtual obstacle-avoidance training with the HoloLens (Coolen et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, more and more research is observed for physical health therapy where exergames have been developed for rehabilitation of patients and results are collected based on physical movements done during the serious game. An approach in [15] focused on the gait and posture of participants. Research such as [15] also shows that gait rehabilitation using a mounted AR headset with a new algorithmic approach called HoloLens can be beneficial for patients especially kids with cerebral palsy (CP).…”
Section: Rq1) What Is the Scope Of Ar In Terms Of Its Uses For Health...mentioning
confidence: 99%
“…The Intra-Class Coefficient between steps length calculated with HoloStep and the reference was 0.92 for children with GMFCS I and 0.86 for children with GMFCS II or III. [23].…”
Section: A Design Studymentioning
confidence: 99%
“…During the session, raw data were logged (100Hz) in .txt format through the application and were available in the Windows Device Portal. Logfile contained time (s), position x, y, and z of the headset, step length, and distance traveled calculated with HoloStep algorithm [23]. The outcomes were: Mean speed (condition MAX and condition INTER), percentage of time spent above the MAX target speed (condition MAX), percentage of time spent around the INTER target speed (± 0.1 m/s) (condition INTER), time to reach the target speed (condition MAX and condition INTER).…”
Section: Outcome Assessmentmentioning
confidence: 99%